1978
DOI: 10.1115/1.3454488
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Compact Cutter Studies for Geothermal Bit Design

Abstract: As a prerequisite to design of a geothermal drill bit using diamond compact cutters, the rock cutting characteristics of these compacts have been studied in a series of instrumented single-cutter continuous and interrupted turning tests on hard, high-compressive strength sandstone and other rocks of known properties. A range of compact rake angles was used and cutting forces were measured. Rake angles affected cutting efficiency (specific energy) at light cuts but were less significant at high penetration forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…As the depth of cut increases, the mean cutting force tends to be lower than predicted by the linear relationship [10]. Rock cutting tests conducted by several researchers on various types of rocks have shown that the optimum back rake angle of PDC bits varies from −5 to −25 • [11][12][13][14]. These and other experimental studies have contributed immensely to the understanding of rock cutting and have provided insights into the mechanisms of rock cutting.…”
Section: Introductionmentioning
confidence: 99%
“…As the depth of cut increases, the mean cutting force tends to be lower than predicted by the linear relationship [10]. Rock cutting tests conducted by several researchers on various types of rocks have shown that the optimum back rake angle of PDC bits varies from −5 to −25 • [11][12][13][14]. These and other experimental studies have contributed immensely to the understanding of rock cutting and have provided insights into the mechanisms of rock cutting.…”
Section: Introductionmentioning
confidence: 99%
“…3 The wear study suggested that increases in temperature result in exponential increases in wear rate. Laboratory wear studies in Jack Fork sandstone showed that PDC cutter wear was dependent on the cutter speed and wearflat temperature.…”
Section: Wear Model Developmentmentioning
confidence: 99%
“…A number of researches aimed to design the crown shape of the PDC bit by employing the principles of equal wear, equal volume of rock removed and power (Glowka, 1985, Hibbs andFlom, 1978). However, they ignored the effect of cutter-rock interaction; therefore, they did not efficiently reflect the force and the cutting wear.…”
Section: Introductionmentioning
confidence: 99%